STATISTICAL STUDY OF ACADEMIC PERFORMANCE OF STUDENTS OF FEDERAL UNIVERSITY KASHERE, GOMBE STATE, NIGERIA - M. B. Mohammed; B.Nata’ala; A.U. Kinafa, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2018)
The aim of this research is to perform some statistical analysis on first year and final year results of Students of Faculty of Science, Federal University Kashere. Some descriptive statistics were computed and Cohen’sKappa Statistic was used to investigate whether the final-year result can be predicted using the first year result of the students. The proposed reliability index gave a value of 0.49 which is considered to be a moderate agreement coefficient. This means that the first year results of the students can be used to predict their final year results fairly accurately. Sixty eight percent (68%) of students retained their first year academic classification on completion of their studies in the University; twenty three percent (23%) improved their first year result on completion while nine percent (9%) regressed.